2019
DOI: 10.1055/s-0039-1688831
|View full text |Cite
|
Sign up to set email alerts
|

Potential of an Electronic Health Record-Integrated Patient Portal for Improving Care Plan Concordance during Acute Care

Abstract: Background Care plan concordance among patients and clinicians during hospitalization is suboptimal. Objective This article determines whether an electronic health record (EHR)-integrated patient portal was associated with increased understanding of the care plan, including the key recovery goal, among patients and clinicians in acute care setting. Methods The intervention included (1) a patient portal configured to solicit a single patient-designated recovery goal and display the care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
(61 reference statements)
0
17
0
Order By: Relevance
“…Better communication between patients and providers was reported as a benefit following the implementation of EHRs/PHRs [32,34,38,42,44,69,86,87,102,134,146,147,153]. Physicians recognized the value of being able to share patient-centered information with patients using EHRs [34,143], while clinicians perceived that new communication channels such as messaging through EHRs should improve communication between patients and providers [45].…”
Section: Communicationmentioning
confidence: 99%
“…Better communication between patients and providers was reported as a benefit following the implementation of EHRs/PHRs [32,34,38,42,44,69,86,87,102,134,146,147,153]. Physicians recognized the value of being able to share patient-centered information with patients using EHRs [34,143], while clinicians perceived that new communication channels such as messaging through EHRs should improve communication between patients and providers [45].…”
Section: Communicationmentioning
confidence: 99%
“…29,30 Providers also may underestimate the utility of patient portals 31 ; many patients are keen to have access and believe portals can improve many aspects of their care, 30 with viewing laboratory results being the most frequently accessed activity on the portal. 32 Portals may increase patient understanding of the care plan 33 ; yet ways to visualize such data provided in portals needs further work to result in more meaningful use. 34 Concerns about data management (security, privacy, and reliability of data), which was a key issue in the 2013 study, 20 was not identified as a major barrier in our study.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…Many of the studies [ 47 , 68 , 77 , 80 , 82 , 100 , 101 , 109 - 112 , 114 ] have explored patient experiences with access to patient portals and subsequently access to their own medical information. All of the studies reported that users were highly satisfied with the access, and in one study, 97% of survey respondents stated that they would definitely or probably recommend the portal to other clients and families [ 110 ].…”
Section: Resultsmentioning
confidence: 99%